DIFFERENTIAL PROTECTION TECHNIQUE OF THREE PHASE POWER TRANSFORMER USING WAVELET PACKET TRANSFORM - HR (NIM 23205006), ISWADI
This thesis explains a technique for differential protection of three phase power transformer using the wavelet packet transform (WPT). WPT is employed to obtain the characteristics of transformer differential current, so that this proposed technique is able to distinguish between internal and external faults and magnetizing inrush. The proposed technique uses differential current as the only input. The technique has been tested and evaluated to 152 data resulted from Matlab/SIMULINK simulation. The data includes differential currents of transformer during normal and faulted conditions. The evaluation to the technique has taken into account the effects of types of wavelet filter, transformer winding connections, and fault and ground resistances. Testing was made using saturated CT model. The evaluation results show that the proposed technique gives good selectivity as indicated by its ability to distinguish between internal and external faults and keep maintaining transformer operation during magnetizing inrush. The technique also gives high speed relay response. In general, its selectivity and speed relay response is insensitive to variation of wavelet filter, transformer winding connections, and fault and ground resistances and immune due to CT saturation.